institutional criticism of academic writing: participatory writing, allegorical reading, experiment interview with James Elkins - Průchová, Andrea (Iluminace, 2016)
An interview with American art historian and critic James Elkins about his projects, modes of communication and professional writing.
Keywords: American historian; critic of art; literature and film